1990
DOI: 10.1128/aac.34.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-dose pharmacokinetics of ofloxacin in serum, saliva, and skin blister fluid of healthy volunteers

Abstract: The pharmacokinetics of ofloxacin were determined in six healthy volunteers after oral administration of 200 mg twice daily for 3.5 days. To study the pharmacokinetic behavior at the target site in bacterial infection of the skin, drug concentrations were determined in suction blister fluid (SBF) Ofloxacin is a fluorinated quinolone exhibiting a marked bactericidal effect by inhibiting DNA gyrase (13, 21). Ofloxacin is active against a wide spectrum of microorganisms, including gram-positive bacteria (11,23,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 23 publications
(28 reference statements)
2
10
0
Order By: Relevance
“…Fujita et al (1995) in their studies on patients with renal impairment had reported a ratio of 1:1 for saliva to serum concentrations. However, Warlich et al (1990) have reported a ratio of 0.6 and a close relation of levels in the saliva and serum (r= 0.99), which is consistent with our findings. The mean saliva/plasma (S/P) ratio of ofloxacin was around 0.6 and this remained the same when ofloxacin was given in any combination.…”
Section: Discussionsupporting
confidence: 83%
“…Fujita et al (1995) in their studies on patients with renal impairment had reported a ratio of 1:1 for saliva to serum concentrations. However, Warlich et al (1990) have reported a ratio of 0.6 and a close relation of levels in the saliva and serum (r= 0.99), which is consistent with our findings. The mean saliva/plasma (S/P) ratio of ofloxacin was around 0.6 and this remained the same when ofloxacin was given in any combination.…”
Section: Discussionsupporting
confidence: 83%
“…Fujita et al 24 in their studies on patients with renal impairment had reported a ratio of 1:1 for saliva to serum concentrations. However, Warlich et al 25 have reported a ratio of 0.6 and a close relation of levels in the saliva and serum (r 5 0.99), which is consistent with other findings. The mean S/P ratio of INH was around 0.15 and this remained the same when INH was given in any combination.…”
Section: Isoniazid Pharmacokineticssupporting
confidence: 89%
“…The coefficients of variation (between-day and within-day) in serum, saliva and blister fluid were less than 3.6% (Warlich et al 1990).…”
Section: Methodsmentioning
confidence: 96%
“…Oral bioavailability of ofloxacin appears to be complete, with 95 to 100% absorbed (Lode et al 1987). Peak serum concentrations are attained rapidly (range 0.5 to 3h) [Bitar et al 1989;Leroy et al 1987;Lode et al 1987;Verho et al 1985;Warlich et al 1990]. The administration of ofloxacin with food delays the time to maximum concentration (tmax) but does not alter the extent of absorption (H6ftken et al 1988;Leroy et al 1987).…”
Section: Absorptionmentioning
confidence: 94%